Investment in Procurement of Mobile Cranes at Kijing Port to Increase Non-Container Production Using Financial Evaluation Method - Yusuf, Mochammad Choiron; Ahyudanari, Ervina (Dinasti Publisher, 2026)
This research is motivated by the significant increase in throughput at Kijing Port Branch, with an average increase of 171% from 2022 to 2024. This growth reflects the increasing demand for loading and unloading services, requiring companies to provide superior service and meet the growing market demand. However, on-the-ground conditions indicate that loading and unloading equipment, particularly key equipment such as mobile cranes, remains very limited. This limitation results in low cargo volumes being served. Therefore, to increase service capacity and maximize market potential, additional loading and unloading equipment and a restructuring of the service system at Kijing Port dock are required. In this regard, a comprehensive investment feasibility study is necessary, both from a financial and operational perspective. This research used secondary data, including production throughput data, and primary data from informants or sources. Using the variables of Investment Value, Rate of Return, Investment Period, Operating Income, and Operating Costs, a feasibility calculation is obtained, including Net Present Value (NPV), Benefit Cost Ratio (B/C Ratio), Profitability Index (PI), Payback Period (PP), and Internal Rate of Return (IRR). These calculations are then tested using sensitivity analysis and potential risks, and the potential increase in non-container cargo handling is calculated. The analysis provides a strong quantitative basis for determining investment strategies based on the NPV, IRR, BCR, PI, and PP. These indicators assist in assessing risk, weighing lease and purchase alternatives, and ensuring that mobile crane investment decisions truly add value to the company.